The Role of Regional Organizations in Building Peace In South Sudan: IGAD As a Model - Alameer, Mohammad Farouq Abd; Al-Kaoud, Israa Sharif (Journal of Ecohumanism, 2024)
Regional blocs are pivotal in fostering peace through preventative measures, diplomatic intervention, conflict resolution, and post-war recovery. These entities have successfully mediated numerous conflicts, including the 2008 Kenyan peace accord, the 2005 Sudan peace deal, and the 2000 Algiers Agreement between Ethiopia and Eritrea. Effective regional peacebuilding hinges on several factors, including unified support from member nations. A clear mandate to address conflicts, coupled with adept mediation skills and international recognition, are essential. Furthermore, adequate financial and human resources are crucial for operational success. The Intergovernmental Authority on Development (IGAD) exemplifies a regional body that has contributed to peacebuilding efforts in South Sudan. The organization has led numerous mediation initiatives and contributed to the achievement of several peace agreements, most notably the Comprehensive Peace Agreement of 2015 and the Khartoum Agreement of 2018, which serves as the current framework for resolving the conflict in Juba. IGAD has actively contributed to the realization of these peace accords. Although obstacles have been substantial, IGAD’s initiatives have yielded concrete advancements in resolving the South Sudanese conflict.